A novel system for measurement of the transverse electron momentum distribution from photocathodes - Feng, J.; Nasiatka, J.; Wan, W.; Vecchione, T.; Padmore, H. A. (Review of scientific instruments, 2015)
The transverse momentum of electrons produced by a photocathode contributes significantly to the performance of several different types of accelerator-based light sources, such as Free Electron Lasers, as well as systems designed for ultrafast electron diffraction and dynamic transmission electron microscopy. Minimization of the transverse emittance from photocathodes is the subject of intensive research, and therefore measurement of this parameter is of great importance. Here, we describe a simple system that offers real time measurements of transverse emittance and can be easily integrated into the photocathode fabrication process.